Akuntansi Hijau dalam Perspektif Literatur Review - Martinus Sony Erstiawan; Tony Soebijono; Sulistiowati Sulistiowati (AKUNTANSI 45, 2024)
The purpose of this research is to explore and examine the management of green accounting as a form of corporate responsibility and to enhance the entity's reputation. The data used is secondary data derived from various studies written by authors and published in accredited national journals. The population used comprises various green accounting studies in Indonesia. The sampling technique in this study is technology-assisted, using the Publish or Perish application edition 8 with sources from Google Scholar. The research method used in this study is a literature review with samples taken from accredited national journals on the topic of green accounting, covering the publication years from 2005 to 2024. The collected data includes volume, issue number, research objectives, keywords, research methods, population, research samples, and conclusions. The results indicate that there are 70 scientific articles spread across SINTA 2 to 6, showing that green accounting research is increasingly popular in academic studies. The positive impact of implementing green accounting on corporate performance can enhance managerial performance and profitability. Suggestions for further research on green accounting are related to corporate governance, managerial performance, corporate reputation, and the sustainability of green accounting.